TEOLOGI, KEKUASAAN, DAN KEADILAN DALAM PERSPEKTIF SEJARAH ISLAM - Rochmat, Saefur (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2008)
Abstract It is very often for some people to define theology as the core of Islamic teachings in the regard of its content as the science of God. It has Arabic similar terms such as Aqidah and Kalam for explaining the principles of God. It is not surprisingly that Moslem should deal with the issues of theology since the early history of Islam, but why do appear some conflicts in the matters of theology. Theological controversies are something inherent regarding theology is the result of man's thinking which are bound by the limits of space and of time as the contexts. In other words, theology is the application of the principle of universalism of Islamic teachings in the certain contexts of space and time. Consequently theology is improperly to be claimed as having a universal application. That is why theology is different from iman (belief). It is believed by the Sufis who evaluate correctly that theology does not have an in-depth feeling of spirituality due to its main focus on the use of ratio for the elaboration. Meanwhile iman exists in all religions theology exists in the religions which deal with the matters of worldly affairs, especially in monotheist religions such as Yew, Christian, and Islam. Theology is in great need at the time of crisis such as at the time of the death of Muhammad PBUH the prophet. Indeed at that time theology has not developed well and be arranged systematically as today. We have some theological groups such as Shiite, Sunni, Khawarij. And in Indonesia we have Muhammadiyah, Nahdlatul Ulama, and PKS which all of them come from the Sunni sect. It is possible to notice them from their different socio-cultural background. In other words, socio-cultural background influence the form of theology. Keywords: theology, belief, Sunni, Shiite, Muhammadiyah, NU, and PKS.